Peran Pelatihan Mental dalam Meningkatkan Sport Confidence Atlet Renang SMP/SMA Ragunan - Juriana (Fakultas Psikologi Universitas Pancasila, 2016)
Sport confidence is important psychology's aspect for athletes to be successful in their performance. Swimmers in SMP/SMA Ragunan are junior talent athletes to accelerate in sports champion. This research examines the role of mental training in enhancing sport confidence of SMP/SMA Ragunan's swimmers. This is qualitative research. The result of this research showed that mental training has active role in enhancing sport confidence of SMP/SMA Ragunan's swimmers. Relaxation and visualization training plays the best role in enhancing sport confidence. This research suggests that Ragunan's swimmers have to continue mental training until they get positive effect in their performance. Besides, sport needs more sport psychologist in the future to give mental training and education program in another kind of sport.